Development of a stable Sf9 insect cell line to produce VSV-G pseudotyped baculoviruses - Plastine, María del Pilar; López, María Gabriela; Gravisaco, María José; Taboga, Oscar; Alfonso, Victoria (Springer Nature, 2024)
Baculoviruses have shown great potential as gene delivery vectors in mammals, although their effectiveness in transferring genes varies across different cell lines. A widely employed strategy to improve transduction efficiency is the pseudotyping of viral vectors. In this study, we aimed to develop a stable Sf9 insect cell line that inducibly expresses the G-protein of the vesicular stomatitis virus to pseudotype budded baculoviruses. It was obtained by inserting the VSV-G gene under the control of the very strong and infection-inducible pXXL promoter and was subsequently diluted to establish oligoclonal lines, which were selected by the fusogenic properties of VSV-G and its expression levels in infected cells and purified budded virions. Next, to enhance the performance of the cell line, the infection conditions under which functional pseudotyped baculoviruses are obtained were optimized. Finally, different baculoviruses were pseudotyped and the expression of the transgene was quantified in mammalian cells of diverse origins using flow cytometry. The transduction efficiency of pseudotyped baculovirus consistently increased across all tested mammalian cell lines compared with control viruses. These findings demonstrate the feasibility and advantages of improving gene delivery performance without the need to insert the pseudotyping gene into the baculoviral genomes.
Keywords: Ciencias naturales::Ciencias biológicas::Bioquímica y biología molecular